The Future of Driving in Developing Countries - Ecola, Liisa (RAND Corporation, 2014)
The level of automobility, defined as travel in personal vehicles, varies quite substantially between countries even at similar levels of economic development. Researchers sought to determine the factors besides economic development that affect automobility, their influence on automobility, and what would happen to automobility in developing countries if they progress along similar paths as developed countries.